Of nature and people : community-based natural resource management and land restitution at Makuleke - Louw, Francois Johannes (Stellenbosch : University of Stellenbosch, 2010)
Thesis presented in fulfilment of the requirements for the degree of Master of Social Anthropology at the University of Stellenbosch